Réfléchir la compétence : approches sociologiques, juridiques, économiques d'une pratique gestionnaire - Morin, Lucie (Relations industrielles / Industrial Relations, 2004)
The article reviews the book, "Réfléchir la compétence : approches sociologiques, juridiques, économiques d’une pratique gestionnaire," edited by Arnaud Dupray, Christophe Guitton and Sylvie Monchatre.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

The Determinants of Participation in Non-Mandatory Training - Renaud, Stéphane; Lakhdari, Mehdi; Morin, Lucie (Relations industrielles / Industrial Relations, 2004)
This article presents an empirical research on the determinants of employees' participation in non-mandatory training offered by their employer. The analysis model identified two groups of determinants, i.e. socio-demographic (age, gender, family responsibilities and education level) and employment-related (organizational tenure, hierarchical position and employment status). Participants, mostly female, were employees from a large Canadian service organization. Results showed that age negatively influenced participation, that women participated more than men, and that the education level was negatively related to participation. Findings also indicated a non-linear relationship between organizational tenure and participation, and that the probability of participation in non-mandatory training increased with the hierarchical position occupied. Family responsibilities and employment status were not found to be significant predictors of participation. [PUBLICATON ABSTRACT]
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Demographics; Employees; Employment; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Training